2009
DOI: 10.1177/026010600902000103
|View full text |Cite
|
Sign up to set email alerts
|

Salt Fortification with Iodine: Sudan Situation Analysis

Abstract: Iodine deficiency disorders (IDD) constitute a severe public health problem in Sudan. IDD affects children and women throughout life. More than 2 out of 10 school age children have goiter. The prevalence reaches 40% in some regions of the country. Several interventional measures were introduced to control the IDD problem. While the situation with regard to production and supply of iodized salt was thus deteriorating, an Emergency Food Security and Nutrition Assessment Survey (EFSNA) revealed that the prevalenc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 5 publications
0
8
0
Order By: Relevance
“…This reflects the low awareness and weak political commitment toward USI and IDD control (18,19). Many ministerial decrees were issued by ministers of health, requesting salt manufacturers to produce iodized salt (18), in addition to legislations banning the sale of non-iodized salt in three states.…”
Section: Discussionmentioning
confidence: 99%
“…This reflects the low awareness and weak political commitment toward USI and IDD control (18,19). Many ministerial decrees were issued by ministers of health, requesting salt manufacturers to produce iodized salt (18), in addition to legislations banning the sale of non-iodized salt in three states.…”
Section: Discussionmentioning
confidence: 99%
“…12 A more recent situational analysis has shown that IDDs still affect children and women throughout the Sudan and that no policy supporting universal salt iodization is in place. 13 Thus, the aim of this study is to evaluate the current status of IDDs in the Sudan and to provide baseline impact indicators for future IDD control programmes. The study also seeks to respond to the 2005 World Health Assembly resolution (WHA58.24) mandating countries to report on their IDD situation every three years.…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, some concerns about USI have circulated, for instance population trends in thyroid illness [1719] and misconceptions about the risks posed by the diet of coastal residents, especially in urban areas. Urban residents believe they have sufficient iodine because they have more access to seafood as they live in coastal regions, and thus they prefer non-iodized salt [20, 21]. In addition, many local salt plants produce coarse salt, which results in consumption of non-iodized salt.…”
Section: Discussionmentioning
confidence: 99%